Syntactic architecture and its consequences III Inside syntax (Volume 11) - Douglas, Jamie; Biberauer, Theresa; Vikner, Sten; Bárány, András (Language Science Press, 2021)
This volume collects novel contributions to comparative generative linguistics that "rethink" existing approaches to an extensive range of phenomena, domains, and architectural questions in linguistic theory. At the heart of the contributions is the tension between descriptive and explanatory adequacy which has long animated generative linguistics and which continues to grow thanks to the increasing amount and diversity of data available to us. The chapters develop novel insights into a number of core syntactic phenomena, such as the structure of and variation in diathesis, alignment types, case and agreement splits, and the syntax of null elements. Many of these contributions show the influence of research by Ian Roberts and collaborators and they provide varied perspectives on current research in synchronic and diachronic comparative syntax. This book is complemented by volume I available at https://langsci-press.org/catalog/book/275 and volume II available at https://langsci-press.org/catalog/book/276.